2012
DOI: 10.1002/pssr.201206081
|View full text |Cite
|
Sign up to set email alerts
|

Density functional study of α–β phase transition of polyvinylidene difluoride

Abstract: We perform density functional calculations to investigate structural and dynamical properties of crystalline polyvinylidene difluoride (PVDF) associated with the transition from α to β phase. We examine the change of the conformational energy and the corresponding structure of each phase depending on the lattice parameters of the orthorhombic crystalline structure. From this information, we construct the path that connects the point where the α phase is most stable to the point where the β phase is most stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…We also observed that dynamical patterns of the dihedral angles for four other simulations (simulations under I-B, -C, -D, and -E) are similar to the one shown under condition I-A. On the basis of the time-dependent behavior of these dihedral angles, we can further deduce that, when mechanical drawing is applied to the PVDF system, formation of the β phase is initiated at two or three monomer units, and it propagates to neighboring units. ,,, Such a mechanism is supported by recent experiments by Li and co-workers, who showed that, under mechanical stretching, the β phase initially emerges in the middle of a spherulite of the α phase, and then the region of the β phase expands as the transition proceeds . Both parts a and b of Figure show that mechanical stretching acting parallel to the chain direction readily transforms the PVDF chain into the all-trans form.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…We also observed that dynamical patterns of the dihedral angles for four other simulations (simulations under I-B, -C, -D, and -E) are similar to the one shown under condition I-A. On the basis of the time-dependent behavior of these dihedral angles, we can further deduce that, when mechanical drawing is applied to the PVDF system, formation of the β phase is initiated at two or three monomer units, and it propagates to neighboring units. ,,, Such a mechanism is supported by recent experiments by Li and co-workers, who showed that, under mechanical stretching, the β phase initially emerges in the middle of a spherulite of the α phase, and then the region of the β phase expands as the transition proceeds . Both parts a and b of Figure show that mechanical stretching acting parallel to the chain direction readily transforms the PVDF chain into the all-trans form.…”
Section: Resultssupporting
confidence: 80%
“…However, the nonpolar α phase is experimentally an in-preparation phase, and mechanical drawing or an external field is required to transform the α phase into the β phase . Many experimental studies have focused on the behavior and efficient conditions for α–β phase transition and on the role of the mechanical drawing and electric poling processes. , The analysis of the contents of the β phase and crystallinity has revealed that, although conformational transformation of the gauche into the trans can be done almost completely without difficulty, the β phase still has low crystallinity. , Most theoretical studies, using force field (FF) methods and density-functional theory (DFT), have focused on the analysis of the phase stability and ferro- or piezoelectric properties. Current interest has been focused on understanding the dynamics associated with α–β phase transition, which requires careful investigation of complicated torsional and rotational motions along the α–β transition route.…”
Section: Introductionmentioning
confidence: 99%
“…[ 216–218 ] One example is the density functional theory (DFT), which is an important tool to calculate the energy changes during conformational transitions of PVDF‐based polymers. [ 219–221 ] For instance, Wang et al. utilized DFT to calculate the phase transformation barrier of PVDF under various electrical fields and found that the energy barrier for the α to β chain transition was ≈16.16 kJ mol −1 , while that from β to α was about 6.24 kJ mol −1[ 222 ] Ranjan et al.…”
Section: Structure Manipulation Of Pvdf‐based Polymers To Improve Pie...mentioning
confidence: 99%
“…A Pb­(Zr,Ti)­O 3 (PZT) ferroelectric field-effect transistor as a NVRAM bit has exhibited a high density along with fast reading and writing speeds at a low operating voltage . Although PZT as a representative ferroelectric material has higher ferroelectric polarization and piezoelectric coefficients than other materials, it contains Pb, which is toxic. In terms of environment friendliness, inorganic lead-free oxides such as BaTiO 3 and BiFeO 3 or organic ferroelectric copolymers such as poly­(vinylidene fluoride- ran -trifluoroethylene) (P­(VDF-TrFE)) are promising candidates for the aforementioned applications. In general, nontoxic and flexible ferroelectric polymers have low crystallization temperatures below 200 °C but lower ferroelectric polarization and piezoelectric coefficients than inorganic ferroelectric materials.…”
Section: Introductionmentioning
confidence: 99%